Study of the Potential of Marine Ecotourism on the Siantan Island of Anambas Regency of Riau Islands Province - Hendra Kharisma; Joko Samiaji; Dessy Yoswaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted in July - August 2018 in the Siantan Island ofAnambas Islands Regency Riau Islands Province.Aim to (1) Know the potential of maritime ecotourism on the island of Siantan, Anambas Islands Regency (2) the strategy of developing maritime ecotourism in the Anambas Islands Regency. The method used in this research was survey method and purposive sampling.Data collected include the selection of respondents, identification of tourist activities and measurement of water quality.The analysis used in this study was an analysis of aspects of supporting marine tourism, tourism suitability analysis, analysis of the economic potential of marine ecotourism, and SWOT analysis.The results of this study indicated that Siantan Island has the potential to be developed as a marine ecotourism area, with the category S1 (Very Appropriate) with tourist suitability index value at station I (87.17%) and II (83.33%).These results indicate that Siantan Island has potential natural resources. The results of the SWOT analysis showed several alternative management strategies that appropriate for the development of marine ecotourism on Siantan Island. The results of the SWOT analysis show several alternative management strategies that  appropriate for the development of marine ecotourism on Siantan Island, the analysis consists of three priorities, namely: 1) Spatial and regional arrangement by establishing a zoning system for marine tourism activities, community activities and management of the coastal environment, 2) Improvement of transportation to tourist sites to make it easier for tourists to come to Siantan Island, 3) improvement of facilities and infrastructure for marine tourism activities.Keywords: Marine Ecotourism, RegionalPotentiaL, Siantan Island